Peer communication about contraception knowledge of early adolescent in urban areas - Kurniawati, Yustina Tyas; Sihombing, Lastdes Cristiany Friday; Ratrikaningtyas, Prima Dhewi (International Journal of Public Health Science (IJPHS), 2023)
Currently, generation Z is 27.94% of the Indonesian population and triggers fulfillment of sexual reproductive health information, including contraception, which should be given of 9-12 years old. This effort is necessary to reduce unwanted pregnancy incidence, free sex, and abortion. A factor potential to influence is peer communication. Determine the relationship between peer communication with contraception knowledge of early adolescents in the urban area of Indonesia. This quantitative study with a cross-sectional design uses the Global Early Adolscent Study’s (GEAS) secondary data. The research subjects were 2,225, which were 7th grade of State Junior High Schools in Bandar Lampung, Semarang, and Denpasar, Indonesia. The relationship between peer communication to contraceptive knowledge considers age, gender, sexual history, economic status, residence, and parental communication. Contraception knowledge is divided into good and poor. Data processing was done with univariable, chi-square, and logistic regression statistical tests and used 95% confidence interval (CI) with a 0.05 significance level. Peer communication significantly related to contraceptive knowledge (p-value <0.001). Other factors that influenced were gender, residence, sexual intercourse, and parental communication, which were statistically significant. Conclusion: About half of the early adolescents have good contraception knowledge, which is three times more likely in adolescent who communicates with peers.